Development of Arabic Language Teaching Materials With 4D Model for the Second Semester at STAI Al-Furqan Makassar - Yusuf, Muhammad (Bulletin of Science Education, 2023)
This article aims to find out and analyze the textbooks used by lecturers in the Arabic language course in second-semester of the Islamic Religious Education Study Program at STAI Al-Furqan Makassar in 2022. This study applies a qualitative approach. Data was collected through observations, interviews, and documentation guided by instruments in the form of guidelines for each technique. Sometimes one type of data is searched using the three techniques at once, and sometimes done separately. The collected data is classified, systematized, and analyzed based on the chosen theory guidance. Determination and development of teaching materials can be applied by collaborating with book authors so that it does not have to be the teacher who writes them. The main principle in using the 4D model is to meet the criteria and structured steps (define, design, develop, and disseminate). They are learning Arabic using Bahasa Arab Elementer book by Prof. Dr. H. Ahmad Thib Raya, M.A., which emphasizes the basic rules of Arabic grammar. Arabic language lecturers should develop it by compiling their own more relevant textbooks. The arrangement of the textbooks should adapt to the 4D model. Keywords: Development Arabic Language, Language Teaching Materials, Arabic Language Teaching